The Effect of Thin Capitalization, Company Size and Capital Intensity on Tax Avoidance - Benedikta Olgaviani Don (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to test and analyze Thin Capitalization, Company Size and Capital intencity, simultaneously and partially against tax avoidance. in IDX 30 Index companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. This type of research is quantitative research, using secondary data. The data analysis method used is a panel data regression test using Ms. Excel and Eviews 9 applications. The population in this study is all IDX 30 Index companies listed on the Indonesia Stock Exchange in the period 2017 to 2021. The data collection technique in this study is a purposive sampling technique with the results of 30 study populations into 13 research samples processed in this study. The results showed that simultaneously Thin Capitalization, Company Size and Capital intencity affect tax avoidance. The size of the company partially affects tax avoidance while the variables Thin Capitalization and Capital intencity partially do not affect tax avoidance. The coefficient of determination shows the contribution of the independent variable of 9.3418% to tax avoidance while the remaining 90.6582% is influenced by other variables that are not contained in this study